Determination of hesperidin in food by ultra performance liquid chromatography / Chee Pui Har - Chee, Pui Har (2013)
Hesperidin analysis in food is a simple application involving chromatographic based technique. Method development and validation was performed in order to study linearity, precision and accuracy of the analytical method. The means recoveries obtained at known concentration of QC sample 1000.85 ppm for Hesperidin using Ultra Performance Liquid Chromatography with relative standard deviation of RSD 0.1%.Linearity for Hesperidin was determined at nine different concentration levels ranging from 4.97 to 50116.30 ppm. Detection and quantitation limits were ranged from 0.09992 ppm and 0.333 ppm respectively. The validated Hesperidin analytical method was applied to the study of Hesperidin in food samples which include fruits, vegetables and commercial fruit juices group. The evaluation of the study was elaborated further in the results recoveries.